Saponin from Periploca forrestii Schltr Mitigates Oxazolone-Induced Atopic Dermatitis via Modulating Macrophage Activation - Luting Zeng; Yingqin Liu; Congcong Xing; Yijie Huang; Xin Sun; Guangchen Sun (Mediators of Inflammation)
Atopic dermatitis (AD) is a relapsing, acute, and chronic skin disease featured by intractable itching, eczematous skin. Conventional therapies based on immunosuppression such as corticosteroids are associated with multiple adverse reactions. Periploca forrestii Schltr saponin (PFS) was shown to potently inhibit murine arthritis by protecting bone and cartilage injury and suppressing NF-κB activation. However, its therapeutic effect on oxazolone-induced atopic dermatitis (AD) and the underlying mechanisms on macrophage are still unclear. The AD-like dermatitis was induced by repeated oxazolone challenge to the skin of BALB/c mice in vivo. Blood and ears were biochemically or histologically processed. RT-PCR, western blotting, and ELISA were conducted to evaluate the expression of macrophage factors. Mouse bone marrow-derived macrophages (BMDMs) stimulated with lipopolysaccharide (LPS) were used as a model in vitro. PFS treatment inhibited AD-like dermatitis development. PFS downregulated epidermis thickness and cell infiltration, with histological analysis of the skin lesion. PFS alleviated plasma immunoglobulin (Ig) E, IgG2a, and IgG1 levels. PFS downregulated the expression of M1 macrophage factors, tumor necrosis factor- (TNF-) α, interleukin- (IL-) 6, monocyte chemotactic protein-1 (MCP-1), and nitric oxide synthase2 (NOS2), and M2 macrophage factors, IL-4, arginase1 (Arg1) and CD163 in AD-like skin, which were confirmed by western blot and ELISA analysis. In addition, PFS inhibited LPS-induced macrophage polarization via the inhibition of the phosphorylation of signal transducer and activator of transcription 3 (STAT3) and nuclear translocation of NF-κB p65. These results suggest that PFS exerted an antidermatitis effect against oxazolone by modulating macrophage activation. PFS administration might be useful in the treatment of AD and inflammatory skin diseases.